ANALISIS MANAJEMEN KURIKULUM, PESERTA DIDIK, PENDIDIK, DAN SARANA PRASARANA MAN 3 MEDAN KELAS X-2 - Nurmayani; Oktaviani, Desi; Wahdini, Dhea; Rosa Aritonang; Khoirunnisa, Widia; Anjani Simamora, Dian; Salsabila Lubis, Fathiyah; Sitanggang, Tiory; Yanti Angelika Siburian (STKIP Subang, 2026)
This research is based on the demand to implement the Pancasila Student Profile in madrasas, which requires teachers not only to teach but also to oversee the development of student character. However, in class X of MAN 3 Medan, there is still a gap between conceptual understanding and the implementation of teacher responsibilities. The purpose of this study is to evaluate the various types of educator responsibilities in managing character development, as well as to identify supporting and inhibiting factors. A qualitative descriptive approach was used through observation, interviews with teachers and homeroom teachers of class X, and documentation of activities at MAN 3 Medan. The main results show that educator responsibilities are realized through program planning, routine habituation, role modeling, and daily evaluation based on observation. The most prominent factors are faith and piety, mutual cooperation, and independence; however, time constraints and lack of resources become obstacles. In short, a more integrated character management system is needed because educator responsibilities have not been managed in a structured manner.